Avaliação analítica e bioanalítica da riparina I - Terto, Márcio Vinícius Cahino (2015)
The riparin I is a alcamida obtained from the Aniba riparia with relevant pharmacological activity. Although pharmacological studies are lengthy, the evaluation of solid state features of this alcamida and pharmacokinetic studies are poorly reported. Thus, this study aimed to characterize the solid state of five lots of riparin I, obtained from the same synthetic process, using different analytical techniques and the development of bioanalytical method for pharmacokinetic studies. The characterization was performed by impurity profile of evaluation tests, using high-performance liquid chromatography with diode array detector (HPLC-DAD), at the molecular level using tests with infrared (IR) and nuclear magnetic resonance (NMR 1H and 13C) and particle level through analytical techniques; differential scanning calorimetry (DSC), thermogravimetry (TG), X-ray diffraction (XRD), scanning electron microscopy (SEM) and pyrolysis coupled to gas chromatography / mass spectrometry. The bioanalytical method for the quantification of Riparin I was developed using plasma of Wistar rats after approval by the Ethics and Animal Research Committee (CEPA) of the Federal University of Paraíba (UFPB), Certificate No. 0308/13, using HPLC coupled to mass spectrometry (HPLC-MS). Lots of riparin I had access to similar chromatographic impurities in HPLC-DAD. The 1H and 13C NMR spectra confirmed the identity of riparin I for the five lots, and reveal the presence of impurities in the 1H spectrum, with RIP-1 set the purest among the evaluated plots. The IR spectrum data corroborate the identity of riparin I. The SEM images show crystals with different crystal habits, possibly by changes in the synthesis process. The DSC data confirmed changes in the crystal structure, where it was observed that the RIP-2 batches and RIP-3 had two characteristic melting endotherms, implying that the samples show crystal mixtures. TG data showed the decomposition process into a single step characteristic of the volatilization of riparin I, data confirmed in pyrograms obtained for the five batches studied. The XRD data confirms the presence of different crystalline structures by the presence of peaks in 2ɵ axis, the angles 12 º, 20-25 º and 34 º, the diffraction patterns of different samples. The characterization of the solid state of lots of riparin I highlights the need for greater control in the synthesis process. For the development of bioanalytical method plasma samples were submitted to preparation with different extraction methods, and the protein precipitation method using 400 uL of MeCN presented the highest percentage of recovery around 85.0 to 95.0% . The validated bioanalytical method is linear in the range of 5.0 to 750 ng / mL. The method of execution time is 6.0 min. The intra day and inter day variability less than 9.5%. The greatest variation in the relative standard error of the mean was of -6.59%. The riparin I was stable in plasma matrix 3 cycles of freeze / thaw, 8 hours after processing, the matrix 5 hours at room temperature and frozen at -20 ° C for 30 days. The developed method is a useful tool for pharmacokinetics studies of riparin I.